A novel isolation structure with flexible joints for impact and ultralow-frequency excitations. (October 2018) - Sun, Xiuting; Xu, Jian; Wang, Feng; Zhang, Shu
Highlights: Propose a novel isolation structure with flexible joints. Introduce Origami mechanism in vibration isolation/protection structure. Utilize asymmetrical nonlinearity to extend the effective isolation bandwidth. Determine the optimal structural parameter of folds for isolation effectiveness improvement. Carry out the experimental prototype with remarkable isolation/protection property. Abstract: This paper proposes a novel isolation/protection structure inspired by structure and forcing method of leg parts of bipeds, the Origami-Joint Flexible (OJF) isolation structure. The vibration performances are studied under impact and ultralow-frequency excitations. According to the mechanical features of the legs of bipeds, the restoring force is considered mainly at the joints. Simulating the structure of bipeds, the flexibility of the proposed structure is realized by using an Origami structure with resilience at its folds. Based on the analysis of potential energy, the restoring and damping forces are nonlinear and symmetrical, depending on both magnitude and direction of motions. Then, solutions for transient and steady states are obtained for different high-energy excitations. Due to the large displacement and strong nonlinearity, the Method of Multiple Scales (MMS) with high-order approximation is utilized for theoretical study. The main theoretical results are verified by experiments. The relevant prototype displays remarkable isolation/protection effectiveness for impact and ultralow-frequency excitations. This study not only shows the advantages of strong asymmetrical nonlinearity of the novel isolation structure with flexible joints but also theoretically explains its control mechanism. Graphicalabstract : Image, graphical abstract